Plume-subduction interaction forms large auriferous provinces - Santiago Tassara (Nature Portfolio, 2017)
The lithospheric controls on giant gold deposits remain unclear. Here, the authors show evidence for native gold in the mantle from the Deseado Massif in Patagonia demonstrating that refertilisation of the lithospheric mantle is key in forming metallogenic provinces.